An Analysis of the Features of Cast Composite Materials Based on Light Alloys Reinforced by Particles - Dan, Olena (Journal of Casting & Materials Engineering, 2022)
Light alloys are widely used in industry and everyday life due to their high physical and mechanical properties, wear and corrosion resistance, as well as low cost. In this regard, the use of light alloys as a basis for composite materials is both justified and expedient. The potential of these materials has not been fully used to this day, despite the growing interest in metal matrix composites and extensive investigations aimed at the development of production technology and the introduction of advanced systems based on light matrices. The article presents a short review of the analysis of the main components of the technology of cast composite materials based on light alloys of aluminum and magnesium reinforced by particles. Particular attention is paid to the choice of the matrix alloy, the type, size and amount of reinforcing particles introduced into it, as well as the thermal-time and kinetic parameters of the process.